Alternative Narratives of the Greek Revolution: An Intellectual Map of Messolonghi (1821–1880) - El Gedi, Panagiotis (The Historical Review/La Revue Historique, 2023)
The relationship between space and time is quite complex, especially when combined with other categories, such as poetry and history. This study takes Messolonghi as a case study and tries to see space in relation to time. In particular, it proposes, on the one hand, to look at Messolonghi as a chronotope and, on the other, to focus on the poetry of the period from 1821 to 1880. The contribution aims to create an “intellectual map” of Messolonghi in which we can integrate both the memoirs of the combatants and the discourse of poetry, arguing that historiography and literature use similar methods during this period. The Appendix lists indicative poetic material around Messolonghi.